Improving Simple Oral Descriptive Monologue Skills Using Video Media for Students - Istiqomah, Istiqomah; Baharuddin, Hendra (Jurnal Dieksis ID, 2022)
This Class Action Research was carried out at SMP Negeri 1 Gemarang in class VIII-A students, the research subjects were 22 students. Researchers collected data using qualitative and quantitative techniques. Data collection using qualitative techniques was carried out by way of interviews, observation while data collection through qualitative techniques was carried out by carrying out pre-tests and post-tests so as to produce an average test score. The results of the average score show that there is an increase in students' English-speaking ability; the average score increased from 71.22 in the pre-test to 76.81 in the post-test I and 85.40 in the post-test II. Based on the description above learning by using video media can improve the skills of expressing simple oral descriptive monologues that are acceptable to class VIII-A students of SMP Negeri 1 Gemarang. The findings in this study is that there is a change in student behavior which is more interested during the teaching and learning process. While there were a few weaknesses, namely the students were very enthusiastic but still constrained by shyness and fear, students were busy while practicing dialogue, in general the authors found an increase in speaking skills even though there were a few mistakes in pronouncing English words (mispronounced).